Fundamentals of Entrepreneurship (ENT300) : Puffy Fluffy Pastries/ Angeli Shima Eli … [et al.] - Eli, Angeli Shima; Ujang, Celine; Jonathan, Escardina Grace; Anyi, Kathryn Do; Bollhassan, Nurul Ainul Assyakirin (2019)
Awareness of high quality baked goods is on the rise. Good baked cakes and pastries is a rare combination of nutrition, convenience, and luxury. Today's consumer has less time to create wholesome, handmade bread, but increasingly appreciates the nutritional and sensory benefits it provides. Freshly baked cakes and pastries never goes out of style.